Antibacterial effect of indene on Helicobacter pylori correlates with specific interaction between its compound and dimyristoyl-phosphatidylethanolamine. (March 2020) - Wanibuchi, Kiyofumi; Takezawa, Motoki; Hosoda, Kouichi; Amgalanbaatar, Avarzed; Tajiri, Kentaro; Koizumi, Yuki; Niitsu, Sakura; Masui, Hisashi; Sakai, Yuki; Shoji, Mitsuru; Takahashi, Takashi; Hirai, Yoshikazu; et al.
Graphical abstract: Highlights: Indene compounds synthetically derived from vitamin D3 are potent bactericidal agents of Helicobacter pylori . The functional group of the indene compounds affects the bactericidal activity against H. pylori . The indene compound is considered to disrupt H. pylori 's biomembranes composed by dimyristoyl-phosphatidylethanolamine. This study demonstrates the specific interaction between low-molecular weight hydrophobic compounds. Abstract: Recent studies by our group have suggested that the vitamin D3 decomposition product VDP1 [(1R, 3aR, 7aR)-1-[(1R)-1, 5-dimethylhexyl]octahydro-7a-methyl-4 H -inden-4-one] confers the potent bactericidal action to Helicobacter pylori by targeting the membranal dimyristoyl-phosphatidylethanolamine (di-14:0 PE). In this study we synthesized a new VDP1 derivative to advance further investigation as for the correlative relationship between VDP1 structure and anti- H. pylori activity or PE vesicle collapse induction activity. The derivative VD3-7 [(1 R, 7a R )-4-fluoro-7a-methyl-1-(( R )-6-methylheptan-2-yl)octahydro-1 H -indene] retained a fluorine atom in place of the oxygen atom of VDP1. The fluorination of the carbonyl portion of VDP1 forfeited the effective anti- H. pylori activity. We, therefore, prepared Coomassie brilliant blue (CBB)-containing unilamellar vesicles consisting of various PE molecular species, and examined the vesicle collapse induction activity of either VDP1 or VD3-7 by detecting the CBB eluted from the PE unilamellar vesicles. VDP1 strongly induced CBB elution from the unilamellar vesicles of rectus -PE retaining the same two fatty acid side-chains shorter than carbon numbers 14, indicating that VDP1 specifically disrupted the vesicular conformation of those PE unilamellar vesicles. Meanwhile, VD3-7 had no influence on the structural stability of any PE unilamellar vesicles. This study obtained additional evidence that VDP1 acts as a bactericidal agent on H. pylori by targeting the membranal di-14:0 PE.